Connect faster with

Register

Signup faster with

|   Education without borders.

# 5(x+2)=4(x+3)

5(x+2)=4(x+3)

Posted in Algebra, asked by dawneika clarke, 6 years ago. 1633 hits.

## 2

5(x+2)=4(x+3)

expand the brackets

5x+10=4x+12

now take the variables to L.H.S and take the Constants to R.H.S

5x-4x=12-10

x=2

Venkat Nagendra Thati - 6 years ago
Ask Venkat Nagendra Thati for further help.

## 1

5(X+2)=4(X+3)

Expand both sides by opening the brackets,

5X+10=4X+12

Now rearranging terms so that terms with Variable X comes on one side and constant terms on other side,

5X-4X = 12-10

X(5-4)=2

X=2

So the value of X=2

vinu omanan - 6 years ago
Ask vinu omanan for further help.

## 0

sol----5(x+2)=4(x+3)

5x + 10 = 4x + 12  ......(expand the brackets )

5x-4x  = 12 -10

x  = 2

amit helekar - 6 years ago
Ask amit helekar for further help.

## -2

5(x+2)=4(x+3)

5x + 10 = 4x + 3 (first we multiply 5(x + 2) and 4(x + 3)

5x - 4x + 10-_ 10 = 4x _-4x + 3 - 10 (now add -4x and -10 on both sides we get)

Furqan Ali - 6 years ago
Ask Furqan Ali for further help.
This answer is incorrect. - Profr. Help & Support 6 years ago
- Just now

## 0

Just now
× Attachments/references, if any, will be shown after refreshing the page.
/homework-help